Effect and Role of Bio-Fertilizer in Agriculture: Promoting sustainable agriculture through bio-fertilizers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bio-fertilizer are one of the best modern tools for Agriculture it is defined as preparations containing liming cells or latent cells of efficient stains of microorganism that help crop plants, uptake of nutrients by their interactions in the rhizophere which applied theory sced or soil. They accelerate certain microbial processes in the soil which argument the extract of availability of nutrients in a form easily assimilated by plants. It is a gift of our modern agricultural science. Bio-fertilizers are applied in the agricultural field as a replacement to our conventional fertilizers. Conventional fertilizers contain composite house hold wastes and green manner.In order to study the combined effect of chemical phosphorus fertilizers those are not as effective a chemical fertilizers. So farmers often try to use chemical fertilizer in the field for crop development. But obviously the chemical fertilizers are not environment friendly. They are responsible for water, air and soil polluting and can spread cancer causing agents. Moreover, they may destroy the fertility of the soil in a long run. Bio-fertilizer, prevent pollution and to make this world healthy for everybody in a natural way. Bio-fertilizer contains microorganisms which promote the adequate supply of nutrient to the host plants and ensure their proper development of growth and regulation in their physiology. Lining microorganisms are used in the preparation of bio-fertilizers only there organisms are used which have specific functions to enhance plant growth and reproduction. There are different types of microorganism which an used in the bio-fertilizers. Bio fertilizers being essential component of organic farming play vital role in maintaining soil fertility and sustainability.